Disposition kinetics of gentamicin following intramuscular (IM) administration in kidney damaged goats - Ahmad, A H; Sharma, L D (The Indian Journal of Animal Sciences, 2012)
Disposition kinetics of gentamicin following single dose (5 mg/kg bw) intramuscular (IM) administration in kidney damaged (renal-impaired )goats was investigated. Kidney in goats was damaged by injecting single IV dose (5 mg/kg bw) of uranyl nitrate. The extent of damage was measured as serum creatinine and blood urea nitrogen levels. A one- compartment model adequately described the plasma concentration time profile, The absorption of gentamicin, following IM administration was rapid, with peak plasma concentration achieved within 30-60 min in renal-impaired goats. Therapeutic concentration (5Âµg/ml) was maintained up to 18hr. An elimination halfÂ·life of 482min was observed. Volume of distribution (Vd/F) was 198.4 ml/kg. Clearance value was 0.26 ml/kg/min. Based on the pharmacokinetic data, dosage regimen in renal-impaired goats was calculated.